Analysis of the operation strategy for Xiaomi’s online and offline markets - Lin Jingxin (SHS Web of Conferences)
The world’s smartphones are developing rapidly, Apple, Huawei, millet, and other products in various countries are outstanding. In addition to Apple occupying the world market, other mobile phone brands have flagship stores in Asia, Europe, Latin America, and other places. Among them, the Xiaomi brand was founded in 2010, and its operating strategy is constantly being optimized and iterated. Focus on creating new products to continuously meet the needs of target customers and create a unique IOT ecosystem to help attract more loyal users. Actively explore customer needs in marketing and solve problems raised by customers. Millet will collect users’ opinions on mobile phones and other products and make adjustments in a short period, which brings a sense of participation to Millet users and is one of the reasons for their high loyalty. Xiaomi opens online stores, official website flagship stores, and offline product experience stores to meet customers’ experience needs. This paper analyzes the marketing strategy of the Xiaomi brand and puts forward suggestions for the future development of the Xiaomi brand for industry reference.